ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI OPINI GOING CONCERN OLEH AUDITOR PADA AUDITEE - Febransyah Febransyah; Hany Sabrina (Jurnal RATRI (Riset Akuntansi Tridinanti), 2022)
This study aims to examine the effect of financial condition, company growth, and company size on going concern audit opinion on manufacturing companies listed on the Indonesia Stock Exchange. This study uses a combination method, namely a combination of qualitative and quantitative. This study also uses secondary data, with documentation data collection techniques. The population in this study are 26 manufacturing companies listed on the (IDX) by observing the 2017-2019 Financial Statements with the sample taken namely the Report Finance in accordance with the criteria set by the author using non-probability sampling method. The data were tested using descriptive statistical tests, classical assumption tests, logistic regression analysis, regression model feasibility tests, overall model testing, hypothesis testing, and the coefficient of determination.The results of this study are as follows: 1) Simultaneously Financial Condition, Company Growth, and Company Size have a significant effect on Going concern Audit Opinion with Fcount 3,093 and the significance value is less than 0.05. And the coefficient of determination is 44.2% while the remaining 55.8% is influenced by other variables not mentioned in this research model. 2) Partially, Financial Conditions have a significant effect on Going Concern Audit Opinions with tcount results of 2.940 and a significance value of more smaller than 0.05. 3) Partially, the growth of the company has a significant effect on the Going concern Audit Opinion with the result of tcount 2,246 with a significance value less than 0.05. 4) Partially, the size of the company has no significant effect on the Going concern Audit Opinion with the result of tcount of -1.474 and a significance value greater than 0.05. So that future researchers can use other variables other than those that the author studied, in order to realize even better research.Keywords:Financial Condition, Company Growth, Company Sizeandt Going concern Audit Opinion